0
$\begingroup$

I am doing maths for fun and stumbled upon this amazing worksheet. The second last question is a Diophantine equation with three variables and the solution ends with the general solution to the equation. I understand everything except how they go from

$$w-6z=2\\w=8+6k\\z=1+k\\x+3y=8+6k$$

to the "general solution of x and y" from the above equation to

$$x=8+3t\\y=2k-t$$

I understand that they get $w=8+6k$ and $z=1+k$ from the solution $(8, 1)$ but how they get to the general solution of x and y is unclear to me.

$\endgroup$

3 Answers 3

0
$\begingroup$

You have $$2x+6y-12z=4$$or$$2(x+3y)-12z=4.$$

So setting $w=x+3y$ we have $$2w-12z=4$$ $$w-6z=2$$ which is the diophantine equation in two variables. The above has general solution $$w=8+6k$$$$z=1+k$$ for $k\in\mathbb Z$. Since substituting gives $w-6z=(8+6k)-6(1+k)=8-6+6k-6k=2$ as required. But we know that $w=x+3y$ so it follows that $$x+3y=8+6k.$$

So choosing $$x=8+3t$$ and $$y=2k-t$$ we see that it indeed satisfies the above equation.


This is called parametrisation. So for instance we can write the line $y=x+2$ to be $$(x,y)=(t,t+2)$$ for all $t\in\mathbb Z$ by setting $x=t$. From above we had $x+3y=8+6k$, now set $x=8+3t$ then we obtain $$x+3y=8+3t+3y=8+6k$$ $$3t+3y=6k$$ so $y=2k-t$.

$\endgroup$
0
$\begingroup$

$x+3y=8+6k$ let $y=t$, then $x=8+6k-3t$, where $t \in \Re$ So the solutions are is $x=8+6k-3t, y=t$.

$\endgroup$
0
0
$\begingroup$

If you put $y = 2k - t$ in $x+3y=8+6k$, you get $x=8+3t$.

So, $(x,y) = (8+3t, 2k-t)$.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.